PENURUNAN NILAI COD PADA LIMBAH CAIR INDUSTRI OBAT BERBAHAN HERBAL DENGAN METODE FOTODEGRADASI TERKATALISIS TiO2 DAN OKSIDASI OLEH KAPORIT - , IKA FITRI KRISNASIWI, Prof. Dr. Endang Tri Wahyuni, M.S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study was conducted to obtain the effective method decreasing COD level of the waste water from herbal medicine industry. The investigated methods were photodegradation catalyzed by TiO2, oxidation using CaOCl as an oxidising agent, and the combination methods with the order of oxidation- photodegradation, and that of photodegradation-oxidation. The photodegradation of organic compounds in the waste water was carried out by irradiating the mixture of the wastewater and TiO2 photocatalyst in the close reactor equipped with the UV-lamp. In this process, the influence of irradiation time and photocatalyst mass were studied. The oxidation was carried out by reacting the waste water with CaOCl. In this oxidation, the reaction time and mass of CaOCl were also optimized. The combination of the two methods in decreasing the COD level was performed at the optimum conditions of each method. The effectiveness of the processes was represented as COD level decreasing. The determination of COD level was conducted using reflux-volumetric bichromatometry method. The research results showed that photodegradation for 24 h and with 75 mg of TiO2 gave the maximum effectiveness in decreasing COD level from 19,556.57 to 2,262.86 mg/L. Mean while using oxidation method, the maximum decreasing COD level, became 1,828.57 mg/L can be achieved when 24 h of time and 75 mg of CaOCl was applied. It was clear seen that the former was less effective in decreasing the COD level than the latter. The combination methods with order of photodegradation- oxidation result in decreasing COD level to be 571.43 mg/L, that is still higher than regulated. The combination methods with the order of oxidation- photodegradation can decrease the COD level into 228.6 mg/L which meets the index quality regulated by the government, i.e. below 300 mg/L. It is recommended to apply the combination methods with order oxidation- photodegradation for treatment wastewater of herbal medicine industry